Sistem Monitoring Air Layak Konsumsi Menggunakan Sensor PH meter, TDS dan LDR berbasis arduino - Andi Yulia Muniar (Celebes Computer Science Journal, 2021)
This research aims to design and build an Arduinobased water monitoring tool. pH sensor (power of Hydrogen) to measure acidity levels, a TDS sensor (Total Dissolved Solid) to measure dissolved solids, an LDR sensor (Light Dependent Resistor) to measure turbidity. The method used is the black box testing method. From the results of tests carried out, the tool can run well as evidenced by the success of the sensor which can send data on the LCD display screen. If one of the sensor values does not meet the standard, the relay will automatically cut off the water flow, so that water cannot be produced before re-filtering the machine. The percentage of pH sensor error is 0.14%, the TDS standard is a maximum of 500 ppm, and the turbidity to meet the 5 NTU standard output value is at least 999.